Improving Critical Thinking Skills through the Video-Assisted Problem Solving Method in Elementary School Students - Nurul Hidayah; Deni Adi Putra; Ishmatun Naila (Yayasan Citra Dharma Cindekia, 2026)
This study aims to (1) describe the application of the Problem Solving method assisted by video media, and (2) improve the of critical thinking skills of grade V elementary school students through the Problem Solving method assisted by video media. The method uses Classroom Action Research (PTK) for two cycles. The subjects of the study were 29 students in grade V of SD Negeri Tambak Wedi 508 Surabaya. Data was collected through observation and test techniques. Quantitative data from observations and tests were analyzed descriptively by calculating the average score and percentage improvement. The results of the study showed an improvement in the quality of method application, especially in the problem formulation and hypothesis submission phases, after scaffolding in the form of structured worksheets and guiding questions. Significant improvements also occurred in students' critical thinking skills. In Cycle I, the majority of students (59%) were in the Sufficient category and 34% in the Need for Guidance category. After the improvement in Cycle II, there was a drastic change, where 59% of students moved up to the Good category and there were no more students in the Need for Guidance category. Observations show. Thus, the Problem Solving method assisted by video media can improve the critical thinking skills of grade V elementary school students. The success of its implementation depends on the proper scaffolding planning and the creation of a supportive learning climate. This study recommends using a similar approach to develop higher-level thinking skills in elementary school students.